182k views
3 votes
The function f is given by


f(x) = (x^(3) + bx + 6)g(x)
where b is a constant and g is differentiable function satisfying g(2) =3 and g'(2)= -1. For what value of b f'(2) =0

a. -7
b. -10
c. -12
d. -22


1 Answer

3 votes

Answer:

d. -22

Explanation:

If F(x) is given by:


f(x)=(x^(3)+bx+6) g(x)

The derivative is given by:


f'(x)=(3x^(2)+b) g(x)+(x^(3)+bx+6) g'(x)

if f'(2)=0


f'(2)=(3(2)^(2)+b) g(2)+((2)^(3)+2b+6) g'(2)=0


3(12+b)-(14+2b)=0


36+3b-14-2b=0


b=-22

User Jeffy Lazar
by
5.2k points